2016
DOI: 10.1142/s0192415x16500130
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Pharmacology ofCarthamus tinctoriusL.

Abstract: Carthamus tinctorius L. is a multifunctional cash crop. Its flowers and seeds are extensively used in traditional herbal medicine in China, Korea, Japan, and other Asian countries, for treating various ailments such as gynecological, cardiovascular, and cerebrovascular diseases as well as blood stasis and osteoporosis. More than 100 compounds have been isolated and identified from C. tinctorius. Flavonoids and alkaloids, especially the quinochalcone c-glycoside hydroxysafflor yellow A, N-(p-Coumaroyl)serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 134 publications
0
74
0
6
Order By: Relevance
“…Carthamus tinctorius L. has multifunctional uses and is being used as a traditional herbal medicine in China, Korea, and Japan for decades. It is used in treatments of various ailments such as gynecological, cardiovascular, and cerebrovascular diseases as well as blood stasis and osteoporosis . Our previous studies have shown that C. tinctorius L. prevents LPS‐induced TNF‐α signaling activation and cell apoptosis by inhibiting JNK1/2‐NF‐kB pathway in H9c2 cardiomyoblast cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carthamus tinctorius L. has multifunctional uses and is being used as a traditional herbal medicine in China, Korea, and Japan for decades. It is used in treatments of various ailments such as gynecological, cardiovascular, and cerebrovascular diseases as well as blood stasis and osteoporosis . Our previous studies have shown that C. tinctorius L. prevents LPS‐induced TNF‐α signaling activation and cell apoptosis by inhibiting JNK1/2‐NF‐kB pathway in H9c2 cardiomyoblast cells .…”
Section: Introductionmentioning
confidence: 99%
“…It is used in treatments of various ailments such as gynecological, cardiovascular, and cerebrovascular diseases as well as blood stasis and osteoporosis. 9,10 Our previous studies have shown that C. tinctorius L. prevents LPS-induced TNF-α signaling activation and cell apoptosis by inhibiting JNK1/2-NF-kB pathway in H9c2 cardiomyoblast cells. 11 In this study, we investigated the effect of CTF extract on LPS-induced FAS receptor and IGF-I signaling pathway in H9c2 cardiomyoblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с лекарственными ятрогениями стал возрождаться интерес к фитотерапии, которая признается одним из самых безопасных методов лечения острых и хронических заболеваний при условии, что этим занимается дипломированный врач, а не сам пациент. Однако данные по научному обоснованию и практике применения фитотерапии при ОП пока в основном представлены в зарубежной литературе [9][10][11][12][13][14][15][16][17][18][19]. В целом данные всех источников свидетельствуют о целесообразности использования тех или иных формул фитопрепаратов для профилактики и лечения ОП.…”
Section: оригинальные статьиunclassified
“…Carthamus tinctorius L. has been used extensively as a traditional herbal medicine in China to treat various conditions, including gynecological, cardiovascular, and cerebrovascular diseases, as well as blood stasis and osteoporosis (Li et al, 2009; Han et al, 2016; Wang et al, 2016; Zhang et al, 2016). Over 100 compounds have been isolated from C. tinctorius L. and identified (Zhang et al, 2016), including hydroxysafflor yellow A (HSYA) as one of main active constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 compounds have been isolated from C. tinctorius L. and identified (Zhang et al, 2016), including hydroxysafflor yellow A (HSYA) as one of main active constituents. Injection of safflor yellow (the main active ingredient of which is HSYA) achieved remarkable clinical effects in patients with cardiovascular and cerebrovascular diseases in China (Zhang et al, 2005; Yang et al, 2009; Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%